Uncertainty and Indifference Curves–A Correction - Borch, Karl (Review of Economic Studies, 1973)
Journal Article Uncertainty and Indifference Curves—A Correction Get access Karl Borch Karl Borch The Norwegian School of Economics and Business Administration Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 1, January 1973, Page 141, https://doi.org/10.2307/2296746 Published: 01 January 1973